Empirical evaluation of a virtual laboratory approach to teach lactate dehydrogenase enzyme kinetics - Booth, C.; Cheluvappa, R.; Bellinson, Z.; Maguire, D.; Zimitat, Craig; Abraham, J.; Eri, R. (2016)
© 2016.Background: Personalised instruction is increasingly recognised as crucial for efficacious learning today. Our seminal work delineates and elaborates on the principles, development and implementation of a specially-designed adaptive, virtual laboratory. Aims: We strived to teach laboratory skills associated with lactate dehydrogenase (LDH) enzyme kinetics to 2nd-year biochemistry students using our adaptive learning platform. Pertinent specific aims were to:. (1)design/implement a web-based lesson to teach lactate dehydrogenase(LDH) enzyme kinetics to 2nd-year biochemistry students(2)determine its efficacious in improving students' comprehension of enzyme kinetics(3)assess their perception of its usefulness/manageability(vLab versus Conventional Tutorial). Methods: Our tools were designed using HTML5 technology. We hosted the program on an adaptive e-learning platform (AeLP). Provisions were made to interactively impart informed laboratory skills associated with measuring LDH enzyme kinetics. A series of e-learning methods were created. Tutorials were generated for interactive teaching and assessment. Results: The learning outcomes herein were on par with that from a conventional classroom tutorial. Student feedback showed that the majority of students found the vLab learning experience "valuable" and the vLab format/interface "well-designed". However, there were a few technical issues with the 1st roll-out of the platform. Conclusions: Our pioneering effort resulted in productive learning with the vLab, with parity with that from a conventional tutorial. Our contingent discussion emphasises not only the cornerstone advantages, but also the shortcomings of the AeLP method utilised. We conclude with an astute analysis of possible extensions and applications of our methodology.